Sine Subtraction Laws on Semigroups
We consider two variants of the sine subtraction law on a semi-group S. The main objective is to solve f(xy∗ ) = f(x)g(y) − g(x)f(y) for unknown functions f, g : S → ℂ, where x ↦ x* is an anti-homomorphic involution. Until now this equation was not solved even when S is a non-Abelian group and x* =...
Main Author: | |
---|---|
Format: | Article |
Language: | English |
Published: |
Sciendo
2023-03-01
|
Series: | Annales Mathematicae Silesianae |
Subjects: | |
Online Access: | https://doi.org/10.2478/amsil-2023-0002 |
Summary: | We consider two variants of the sine subtraction law on a semi-group S. The main objective is to solve f(xy∗ ) = f(x)g(y) − g(x)f(y) for unknown functions f, g : S → ℂ, where x ↦ x* is an anti-homomorphic involution. Until now this equation was not solved even when S is a non-Abelian group and x* = x−1. We find the solutions assuming that f is central. A secondary objective is to solve f(xσ(y)) = f(x)g(y) − g(x)f(y), where σ : S → S is a homomorphic involution. Until now this variant was solved assuming that S has an identity element. We also find the continuous solutions of these equations on topological semigroups. |
---|---|
ISSN: | 2391-4238 |